The Sister Village Program: Promoting Community Resilience after Merapi Eruption - Vita Elysia; Ake Wihadanto (Department of Urban and Regional Planning, Universitas Diponegoro, 2018)
Local Government of Magelang Regency initiates the Sister Village Program after Mount Merapi Eruption in 2010. The idea of this program is to connect villages at risk from Merapi eruption to partner villages with less risk in the surrounding regions. This program is part of post-disaster recovery initiatives at the local level which includes planned evacuation routes, shelters, provision of food and other daily essentials. This paper aims to shed light on the role of sister village program in promoting community resilience after the volcanic eruption of Merapi. It is found that the system of sister village program can fulfill many aspects of community resilience components. Considering Indonesia is one of the most disaster-prone countries in the world, this program should be regarded as a good example to be replicated in other prone areas in the country.